DETERMINATION OF CHAMBER AND PISTON GEOMETRY FOR A ROTARY TYPE EXPANSION MACHINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article deals with the determination of chamber and piston geometry for a rotary expansion machine. Analytical expressions for the working surface area of piston and for chamber volume are derived. Three defining parameters of the expansion machine were obtained: gas dynamic machine constant Cp; constant M0 connecting torque and Cp; the main dimensionless parameter of the machine Q0, which relates the volume of the chamber and the torque.